Teacher Creativity to Develop Student’s Collaboration Abilities - Rahayu, Isnaini Umi; Kusumaningrum, Desi Eri; Nurabadi, Ahmad; Triwiyanto, Teguh (Universitas Negeri Malang, 2024)
The aim of this research is to describe (1) teacher creativity in classroom management, (2) theimpact of group learning in developing students' collaboration skills, (3) the approach taken by teacherstowards students. Data collection techniques use interviews, observation and documentation. The resultsof this research are (1) teacher creativity in classroom management in the form of learning agreements,providing motivation, class mastery, use of teaching media, class design, use of the surroundingenvironment, (2) the impact of group learning in increasing students' collaboration abilities in the form ofactiveness, responsibility , accepting consequences, conducive, cooperation between members, this comesfrom mapping based on interests, learning styles and learning readiness, (3) the approach taken byteachers to students in the form of conducting diagnostic assessments, personal approaches, talents andinterests approaches, drawing information from previous teachers, seeking information from parents,learning outcomes, special guidance Keywords: teacher creativity; class management; collaboration skills